Believing in the Church: Why Ecumenism Needs the Invisibility of the Church - Littlejohn, Bradford (Religions, 2019)
Amidst the plethora of approaches to ecumenical dialogue and church reunion over the last century, a common theme has been the depreciation of the classic Protestant distinction between the "visible" and "invisible" church. Often seen as privileging an abstract predestinarianism over the concrete lives and structures of church communities and underwriting a complacency about division that deprives Christians of any motive to ecumenical endeavor, the concept of the "invisible" church has been widely marginalized in favor of a renewed focus on the "visible" church as the true church. However, I argue that this stress on visible unity creates a pressure toward institutional forms of unity that ultimately privilege Roman Catholic ecclesiologies at the expense of Protestant ones, and thus fails of its ecumenical promise. Renewed attention to Reformational understandings of the relationship between divine grace and human action and the centrality and uniqueness of Christ as the foundation of the church, I argue, dispels some misunderstandings of the church's "invisibility" and demonstrates the indispensability of the concept. I argue that this Reformational framework, which refuses to accept the empirical divisions of the Church as definitive and summons us to an ecumenism that belongs to the church's sanctification, provides the best theological ground for ecumenical endeavor.